Anaplastic thyroid carcinoma and foscarnet use in a multitarget treatment documented by 18F-FDG PET/CT: A case report. Issue 6 (February 2017) - Giannetta, Elisa; Isidori, Andrea M.; Durante, Cosimo; Di Gioia, Cira; Longo, Flavia; Tombolini, Vincenzo; Bulzonetti, Nadia; Graziadio, Chiara; Pofi, Riccardo; Gianfrilli, Daniele; Verrienti, Antonella; Carletti, Raffaella; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Rationale: The case reported the rapid remission of disease recurrence achieved adding foscarnet, a DNA polymerase inhibitor that interacts with fibroblast growth factor 2, to low molecular weight heparin and sunitinib for the first time in a patient with an anaplastic thyroid cancer (ATC). Patient concerns: A 65-year-old woman with a multinodular goiter referred for a rapid enlargement of a nodule. Histological examination revealed an ATC with a little area of papillary thyroid cancer (PTC). The patient was resistant to selective single-target treatment. DIagnoses: Immunophenotyping and gene analyses found a significant increase in FGF2 and FGFR1 expression in the primary ATC area (FGF2 = 38.2 ± 6.2% in ATC vs 34.6 ± 6.0% in the differentiated area of PTC, P < 0.05; FGFR1: 41.7 ± 6.0% in ATC vs 34.4 ± 4.2% in PTC, P < 0.001) and in metastatic neck lymph nodes ( P < 0.001 vs normal control tissues). Unlike conventional imaging, 18 F-FDG PET/CT with PERCIST 1.0 criteria promptly and quantitatively detected disease recurrence and remission before and after multitarget therapy, combining anatomic, metabolic, and functional data. Interventions: Foscarnet was administered given the positivity for FGF2, FGFR1 and FGFR4 in ATC. Low molecular wight heparin and Sunitinib were coadministere to limiti metastatic progression and on neck tumor masse, respectively. Outcomes: The rationale for the clinical response to this innovative multitarget association with foscarnet is based on the histological and genetic finding that fibroblast growth factors and their receptor super-family are up-regulated in the primary anaplastic thyroid tumor and in the metastatic lymph node of our patient. Lessons: We propose that fibroblast growth factors and their receptor super-family play a key role as potential therapeutic targets in anaplastic thyroid cancer and the positive relevance of this suggestion for patient care, especially for an individualized management.